Design and fabrication of MEMS optical switches - Li, Jing (2008)
This thesis focuses on the research related to the microelectromechanical systems (MEMS) optical switch consisting of three major areas, micromahined actuator, deep reactive ion etching (DRIE) fabrication, and total internal reflection (TIR) optical switch.